Traversing the Nenbutsu: The Power of Ritual in Contemporary Japanese Buddhism - Gillson, Gwendolyn (Japanese journal of religious studies, 2019)
Japanese Buddhism is often disparagingly called "funeral Buddhism" due to its supposed focus on death care. This is accompanied by a belief that contemporary Buddhism is spiritually bankrupt, merely carrying out meaningless rituals. However, the women in the Bukkyo josei no tsudoi and the nenbutsu meeting affiliated with the Jodoshū, one of the sects of funeral Buddhism, reveal how contemporary Buddhist women actively work through ritual to create meaningful relationships with one another. Utilizing Catherine Bell's concept of ritualization and Ronald Grimes's concept of ritual phases, this ethnographic study shows how the different phases of the meetings work together to create both formal and informal ritual that is intentional, effective, and important to the women who perform it. These women illustrate the enduring dedication to traditional Buddhist ritual practices that they see as important for personal and spiritual growth.